Bioethics teaching in university education - Llacsa Soto, León (2019)
It is based on the need for the teaching of bioethics, its development, in all professions and not only in health. That its objective is to generate knowledge, learning, reflections, attitudes and social ethical behavior. Its methodology emphasizes problem-based learning, favoring ethical reasoning, changing attitudes and teamwork; Seminars and case studies as the most used. It is concluded that at the university, training in bioethics is essential to improve educational quality, promote ethical behaviors with meaning, personal, professional and social; that learning based on problems, seminars, case studies, among others, allow learning that respects values, rights, democracy and environment. Likewise, social responsibility for the quality of education is a function of institutional management and its actors.